Tasks based on graphic humor as a way to develop mathematical communication - Menezes, Luís (2018)
In this paper, I present an exploratory study that seeks to understand the role that tasks based on graphic humor can play in the learning of Mathematics, particularly as far as the students’ written communication is concerned. To be able to achieve this goal, the HUMAT Research Project (Humor in Mathematics Teaching) allowed us to design mathematical tasks based on graphic humor (comic strips) which were used in a 4th grade class (composed of 24 students). The current study follows a qualitative and interpretive methodological approach. Data were collected through the observation of the students’ actions (audio recording of classes were used) and through the analysis of their written records. The results of this study show that mathematical tasks inspired by graphic humor can be taken seriously in Mathematics classes since they are important to promote students’ enthusiasm, their mathematical thinking and mathematical writing.